Psychometric properties of the Stress Coping Scale Brief-COPE 28 in a Peruvian population - Neicer Joel Delgado-Requejo; Julio Cesar Castillo Ramos; Lourdes Carolina Cerda Sánchez (Interacciones)
Background: The highly stressful events we are currently experiencing require great cognitive and emotional effort and affect the mental health of the population. In this sense, coping with stress provides evidence of how people use their resources to cope with or avoid stressful events, which requires validated and reliable instruments to measure accurately. Objective: To determine the psychometric properties of reliability and validity of the BRIEF COPE 28, Spanish version. Method: The design used was instrumental; 530 people participated, 60% men and 40% women, between 18 and 60 years old, from different regions of Peru, selected by non-probability convenience sampling. Results: It is evident that the alpha coefficient of coping styles ranges from α ordinal = 0.74 to 0.82; while in strategies it was between α ordinal = 0.59 to 0.90. In terms of internal structure, the four-factor model obtained a good fit SB-χ²/gl=1.836; CFI=0.92; TLI=0.90, SRMS=0.09 and RMSEA=0.10. A good fit was found with the ten coping strategies model SB-χ²/gl=1.902; CFI=0.96; TLI=0.95, SRMS=0.056, RMSEA=0.069. Conclusion: COPE 28 has good internal consistency; and the model with the four coping styles is inconclusive, while the model with ten strategies has adequate goodness of fit.